Baculentulus kulsarinae sp. nov. from Thailand (Protura: Acerentomata, Acerentomidae) - Likhitrakarn, Natdanai; Nakamura, Osami; Wiroonrat, Wassana; Suttiprapan, Piyawan (Zootaxa, 2016)
Proturan fauna of Thailand has so far been poorly known, only two contributions being hitherto published. Imadaté (1965) recorded 26 species from around the country and Nakamura and Likhitrakarn (2009) reported eight species including three new species from Doi Suthep-Pui National Park, Chiang Mai Province.